Optimization of Water Absorption and Mechanical and Thermal Behavior of Polylactic Acid/Chitosan/Titanium Carbide - S. Krishnamohan; Harishchander Anandaram; V. Rathinam; S. Kaliappan; S. Sekar; Pravin P Patil; Asheesh Kumar; Venkatesan Govindaraajan (Advances in Materials Science and Engineering)
Nanocomposites are being studied for their mechanical, thermal, and water absorption capabilities. Polylactic acid/chitosan blends have been studied extensively for their physical, mechanical, and morphological properties. Although the three materials have been blended, no research has been done on the mechanical or morphological properties of PLA/CS/TiC NPs. PLA/CS bonding is quite deprived, and thus researchers are trying to improve it by introducing TiC NPs; this would improve the composites’ overall quality (mechanical and thermal characteristics as well as water absorption) by increasing the strength of the bind between the two materials. The impacts of TiC NPs on PLA/CS properties are studied using FTIR and XRD and thermal (TGA) and mechanical investigations. Titanium carbide nanoparticles in the polylactic acid/chitosan matrix increase the mechanical characteristics of the materials. As an outcome, the TiC content in the sample rises to 4 wt % even though adding TiC NPs increased the mechanical properties by up to 2%. The findings of this study might be applied to the development of environmentally friendly casings.